THE ROLE OF FUTSAL COACH LEADERSHIP STYLE AND ORGANIZATIONAL SUPPORT ON THE ACHIEVEMENT OF FEMALE FUTSAL ATHLETES AT THE UNIVERSITY CHRISTIAN OF INDONESIA - Alviranti, Alviranti Syasalbilla; Nenny Anggraini; Jonny Siagian (Universitas Kristen Indonesia, 2024)
The achievement of an achievement in the field of sports organization is essentially an accumulative result of various aspects/elements that support the realization of achievement. A leadership style is essential for an organization to improve athletes' achievements, while organizational support is also important in an organization's efforts to improve achievements, as well as to improve its performance. This study has a purpose to find out the role of futsal coach leadership style and organizational support for the achievements of Indonesian Christian University Women's UKOM athletes. The data analysis method used in this study is qualitative descriptive. The study used primary data and secondary data that researchers collected through observation, interviews and documentation. After obtaining the required data, researchers use the validity of the data, which is source triangulation, proving that the research done is actually scientific research and to test the data that has been obtained. The result of the study is that the role of the leadership style of the coach that the leadership style has a very large role to the achievements of athletes and the support of the Indonesian Christian University Futsal Women's UKOM organization is very influential to the achievements of athletes. The leadership style applied to this organization is the authoritarian leadership style combined with democratic leadership style, in addition to the leadership style applied, there is organizational support given by UKOM Futsal Putri Christian University Indonesia more prominently in the field of justice. Keywords: Athlete’s achievement, Leadership Style, Organizational Support